Pemanfaatan Abu Sekam Padi Sebagai Substitusi Semen Pada Bata Ringan - Noprian; Herman Parung; Desi Sandy (Program Studi Teknik Sipil UKI Paulus-Makassar, 2021)
Utilization of rice husk ash as a cement substitute for lightweight bricks is intended to reduce the use of cement as well as an alternative way of managing waste and is expected to have a positive impact on the environment. This study aims to determine the magnitude of the effect of rice husk ash substitution with variations of 0%, 12%, 15%, 17% and 20% and 40% foam agent on the compressive strength, specific gravity and absorption of lightweight bricks. The lightweight brick test includes testing for compressive strength, specific gravity and absorption with 45 specimens measuring 23 x 11 x 5.5 cm and carried out at the Laboratory of Materials and Concrete Structures Technology majoring in Civil Engineering, Indonesian Christian University Paulus Makassar. The results of the specific gravity test of rice husk ash variations 0%, 12%, 15%, 17% and 20% respectively 1451.67 kg/m3, 1358.2465 kg/m3, 1300.7546 kg/m3, 1281.5906 kg /m3 and 1207.3302 kg/m3 and the results of the compressive strength test at 28 consecutive days were 1.9104 MPa, 1.6469 MPa, 1.2516 MPa, 1.2516 MPa and 0.7906 Mpa, as well as the results of the water absorption test respectively 18,8625%, 20,6042%, 25,8885%, 30,0007%, 31, 9233%. The effect of rice husk ash as a substitute for cement can increase water absorption and reduce the compressive strength and specific gravity of lightweight bricks.